Mang Ntat Mascot as branding strategy of Statistics of West Java Province - Saleh, Andri; Setianti, Yanti; Budiana, Heru Ryanto (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
Since 2018, the Statistics (BPS) of West Java Province has used mascots as a branding strategy. This strategy is carried out to build statistical awareness among the people of West Java. Other facts show that the community still does not know much about BPS and rejects data collection. The impact can be seen in the low percentage of the census and survey response rates organized by BPS. This research uses mascots to analyze the branding strategy process carried out by BPS of West Java Province. The method used in this research is a descriptive method with a qualitative approach. Data were collected through in-depth interviews, observation, and documentation from the Public Relations Team of BPS of West Java Province. This research revealed that the mascot of BPS of West Java Province, named Mang Ntat, was created by considering the representation of BPS of West Java Province agencies and the culture of Sundanese society. Mang Ntat mascot appears in various official activities of BPS of West Java Province and official social media content. The results showed that the use of the Mang Ntat mascot as a branding strategy of BPS of West Java Province has not been effective. In the last four years, it has tended to decrease in census and survey activities. It means that the use of the Mang Ntat mascot as a branding strategy of BPS of West Java Province has not been able to build statistical awareness among the public, especially the people in West Java.